Study on the of Staphylococcus and Salmonella in frozen fish in fillets in Rio de Janeiro - Robbs, Paschoal Guimarães; Barros, Glênio Calvancanti de; Solé-Vernin, Carlos (Pesquisa Agropecuaria Brasileira, 2014)
A study of the sanitary quality of frozen fish fillets commercialized in Rio de Janeiro, Brazil, was carried out through the examination of 34 samples, representative of 10 commercial brands. Among the examinated samples, 17 (including eight commercial brands) presented Staphylococcus coagulase positive, but in only four, the counts were superior to 100 Staphylococcus cells per gram. Phage typing of the cultures of the isolated microorganisms showed the following types: 53, 6/47/53/54/75, 53/54, 3C/55, 29/52/52A/80/42D/84, 3A, 81, 81/6, 29/81, 79 e 29/52. There was no detection of Salmonella in all the examinated samples.